Exploring the Financial Dimensions of Lebanese SMEs: Comparative Study between Family and Non-family Business - El-Chaarani, Hani; El-Abiad, Zouhour (International Review of Management and Marketing, 2019)
This study investigates the financial dimensions of family and non-family SMEs in Lebanon from 2005 to 2016. Based on 81 family SMEs and 45 non-family SMEs, the results reveal that family SMEs have outperform the non-family SMEs during economical and political instability period. In addition, the results show that family SMEs rely on long term debts more than non-family SMEs. Oppositely to non-family SMEs, when the level of risk increased with local and regional instability in the period between 2005 and 2011, the results reveal that family SMEs enhanced their needs of financial resources by developing their long term debts and lowering their short term debts. Finally, the results show that family SMEs have more capacity than non-family SMEs to preserve their performance and increase their effort by selecting an overinvesting strategy during instability periods. Keywords: Family firms, SMEs, Financial strategy, Capital structure, Investment JEL Classifications: G3, G24 DOI: https://doi.org/10.32479/irmm.7976